2018
DOI: 10.3390/geriatrics3030041
|View full text |Cite
|
Sign up to set email alerts
|

The Resurgence of Home-Based Primary Care Models in the United States

Abstract: This article describes the forces behind the resurgence of home-based primary care (HBPC) in the United States and then details different HBPC models. Factors leading to the resurgence include an aging society, improved technology, an increased emphasis on home and community services, higher fee-for-service payments, and health care reform that rewards value over volume. The cost savings come principally from reduced institutional care in hospitals and skilled nursing facilities. HBPC targets the most complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 17 publications
0
56
0
Order By: Relevance
“…Caregiver support also featured as an important stressor, which is unsurprising given the frequent dependence of complex homebound patients on others [16]. As financial support/reimbursements for HBPC providers was cited as a major stressor, ongoing future policy reform targeting this aspect could improve health care spending, as HBPC has been shown to be cost-effective in complex patients [1,3,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiver support also featured as an important stressor, which is unsurprising given the frequent dependence of complex homebound patients on others [16]. As financial support/reimbursements for HBPC providers was cited as a major stressor, ongoing future policy reform targeting this aspect could improve health care spending, as HBPC has been shown to be cost-effective in complex patients [1,3,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of another large academic HBPC practice showed similar outcomes, with decreased costs to Medicare, hospitalizations, Emergency Department (ED) visits and Skilled Nursing Facility (SNF) admissions [4]. In the 1980s and 1990s, the number of house calls decreased precipitously, but since that time there has been an increase in the number of house calls performed [5]. Furthermore, HBPC is not only gaining traction in the United States but has also begun to grow internationally as well [6].…”
Section: Introductionmentioning
confidence: 99%
“…In HBPC, healthcare providers (e.g., physicians, NPs, and physician assistants) and interdisciplinary care team provide comprehensive longitudinal in-home medical care to homebound. 16 , 17 In home-based palliative care, the focus is on symptom control and entails the provision of consultative palliative care in collaboration with the patient's primary care provider. 18 In transitional care programs, patients transitioning from the hospital to the home setting receive transitional care home visits by a master's prepared advanced practice nurses such as clinical nurse specialist, more recent forms of the transitional care programs utilize NPs.…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 100,000 homebound individuals in Canada, for whom access to primary care is a challenge (Stall et al 2013); and a recent study, by Heale et al (2018), showed that chronic disease management often suffers when patients with limited resources are obliged to travel to a clinic for care and there are no alternatives. Homebound individuals and those with chronic diseases are more likely be hospitalized and use the emergency room (Densai et al 2008, Norman et al 2018, Woolf et al 2015; whereas, research demonstrates that house calls result in reduce use of both the emergency rooms and hospitals (Chapman et al 2018, Schuchman et al 2018.…”
Section: Introductionmentioning
confidence: 99%